Pengembangan Bahan Ajar Sosiologi Terintegrasi Kearifan Lokal Masyarakat Timor sebagai Materi Penunjang Pembelajaran Sosiologi di SMA - Arsyad, Arifin; Ramlah, ST (CV. Creative Tugu Pena, 2022)
This study aims to develop sociological teaching materials based on local wisdom because there are not many sociological teaching materials available based on local wisdom and these teaching materials are expected to be feasible to use. And this is the important thing that the author wants to research so that local wisdom is taught to students which is developed in supporting materials for learning sociology, so that the local wisdom of the people of East Nusa Tenggara can be preserved, especially on the island of Timor. This study uses a research design for the development of the Borg & Gall (1989) and Kemp & Dayton (1985) models consisting of; (1) research and data collection, (2) planning, (3) preparation of teaching materials, (4) expert validity test, (5) product revision, (6) small-scale field trial, (7) product revision, (8) large-scale trial, (9) revision of the final product, and (10) dissemination and implementation. The feasibility test by material experts reached 88%, while the media expert's assessment reached 91%, this percentage if converted means that the teaching materials developed are very good and feasible to be implemented as supporting materials for learning sociology in high school. The feasibility test based on student response questionnaires reached 83%. The teaching materials developed were very practical to be used by students in obtaining sociological learning support materials, besides that students felt happy learning to use teaching materials, teaching materials provided information on Timorese local wisdom, and teaching materials motivated students to learn. and learn the local wisdom of Timor. Keywords: Teaching Materials, Timorese Local Wisdom, Learning Sociology